EVALUASI PROSES PENGOLAHAN KACANG MENTE CV. CENTRA PRODUKSI MENTE MADURA DESA JELBUDAN SUMENEP - Ach Cholid Syaifullah; Ratih Yuniastri; Rika Diananing Putri (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2021)
Cashew nut (Annacardium occidentale L.) is a versatile plant. In addition to being a source of community income, it is also very suitable for use in the conservation of critical and arid lands, CV Centra Madurese Cashew Production is a business unit that buys cashew nuts and resells them in raw and processed form. Processed cashew products from CV Centra Madura Cashew Production are fried and roasted cashew nuts with various flavors. In running a food business, companies including MSMEs need to continue to make improvements to be able to meet consumer needs. This study aims to evaluate the cashew nut processing process at CV Centra Madura Cashew Products as an effort to develop and improve the cashew nut processing business, especially in the application of product hygiene and sanitation. The research was conducted by survey method by direct observation and conducted by in-depth interviews. The results showed that the cashew processing process that needs to be improved and lacking in the application of hygiene and sanitation is the drying process for cashews. The cashew drying process is carried out on the floor with a tarpaulin plastic base so that it is very susceptible to dust, air pollution and is close to the way in and out of employees at CV Centra Madura Cashew Production.